Investigation of Structural and Mechanical Properties of Nanostructured TiMgSr Alloy for Biomedical applications - Basavarajappa, Pradeep Navilehal; Hegde, Muduvalli Mahabala Rajath; Rajendrachari, Shashanka; Surendranathan, Attukalathil Orongil (Amg Transcend Assoc, 2023)
In this study, Nanostructured TiMgSr alloy is produced by cold Isostatic Pressing (CIP) followed by microwave sintering. The fabricated alloy results in the formation of solid binary solutions along with the elemental phases. The CIP compacted alloy was characterized using X-ray diffraction (XRD) and scanning electron microscopy (SEM) to investigate the phases and the morphology. The presence of intermetallic phases SrTiO3 and Mg17Sr2 along with elemental Ti, Mg, and Sr crystallites with a narrow peak during the sintering process is prevalent; however, the crystallite size was retained in the nanoscale regime around 58 nm. The developed titanium alloy exhibits a low Young's modulus and good strength. The young's modulus of Ti-Mg-Sr alloys was around 48.11 GPa, significantly closer to human cortical bone (10-30 GPa). Among so far developed Ti-based alloys, the CIP consolidated Ti-Mg-Sr alloy results in low young modulus and hardness. In the future, it may be used practically for biomedical applications.
Keywords: Xrd; Nanohardness; Cold Isostatic Pressing (Cip); Young's Modulus; Timgsr Alloys